Nivolumab plus regorafenib in patients with small bowel adenocarcinoma: A case report. Issue 4 (29th January 2021) - Zhang, Gairong; Lin, Li; Dong, Dapeng; Qiu, Hui; Liu, Tao; Lian, Li; Shen, Ge
Abstract: Introduction: Small bowel adenocarcinomas (SBAs) are rare cancers that have a distinct clinical characteristic and genetic profile. The only potentially curative treatment for localized SBAs is surgery, and treatment options are limited for patients in the advanced stage of disease. Patient concerns: A 39-year-old woman presented in October 2015 with a complaint of persistent vomiting for 8 months. Diagnosis: The patient had obstruction caused by a 3 × 2 cm mass at the ascending part of the duodenum and suspected metastasis in the right adnexal region. Postoperative pathology showed a moderately differentiated adenocarcinoma with serosal invasion. The diagnosis was stage IV duodenum adenocarcinoma with right adnexal metastasis. Interventions: After the failure of multi-line treatment with chemotherapy and targeted therapy, she was treated with the immune checkpoint inhibitor nivolumab plus regorafenib. Outcomes: Disease control lasted for 15 months with markedly improved symptoms. Conclusion: To the best of our knowledge, this is the first case of small bowel adenocarcinoma that has been treated with nivolumab combined with regorafenib. This case highlights the potential efficacy of combining nivolumab and regorafenib in the treatment of SBAs.